The Impact and Risk Factors of Screen Time Exposure in Children with Autism Spectrum Disorder - Shahad Ali Ahmed AL-Baldawi; Nabeeha Najatee Akram; Zahraa Aqeel Abdulmajeed (Al-Anbar Medical Journal)
Background: Children with autism spectrum disorder (ASD) are increasingly exposed to screens that correlate to negative health effects.Objectives: To identify possible risk factors associated with long screen viewing in ASD children and identify the effects of prolonged screen time.Materials and methods: A cross-sectional study recruited children with ASD who were followed in the Psychiatry Department in the Central Child Teaching Hospital, Baghdad, Iraq over 7 months. For all children, personal data (age, age at diagnosis, sex, sleeping duration at day and night, and aggressive behavior) and both parents' data (age, educational level, and occupation) and screen data (duration of screen exposure, type of device used for, and the content of screening) were collected for each participant.  Results: A total of 138 children with a mean age of 5.25 ± 2.85 years were included in the study with a male-to-female ratio of 5.6:1. One-third of ASD children had long-duration of screen exposure (≥ 2 hours per day). Although none of the studied patient’s characteristics was related to the duration of screen exposure, two maternal factors were significantly related to the longer duration of screen exposure (lower level of education and being a housewife with P-values of 0.008 and 0.02 respectively). Children diagnosed at younger ages are subjected to a higher duration of screen exposure with a correlation coefficient r = - 0.337 and P-value = 0.027.Conclusion: Maternal level of education and occupation represent significant determinants of screen time in children with ASD. Long screen exposure in ASD children correlates with the patient’s age at diagnosis but has a non-significant effect on their social communication.